2018
DOI: 10.1007/s00198-018-4694-3
|View full text |Cite|
|
Sign up to set email alerts
|

Notch in skeletal physiology and disease

Abstract: Notch (Notch1 through 4) are transmembrane receptors that play a fundamental role in cell differentiation and function. Notch receptors are activated following interactions with their ligands in neighboring cells. There are five classic ligands termed Jagged (Jag)1 and Jag2 and Delta-like (Dll)1, Dll3, and Dll4. Recent work has established Notch as a signaling pathway that plays a critical role in the differentiation and function of cells of the osteoblast and osteoclast lineages and in skeletal development an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 99 publications
1
78
0
Order By: Relevance
“…Notch 2 was previously found to play a major role in suppression of osteoblastogenesis and promotion of osteoclastogenesis . This effect was mostly exerted by induction of RANK in cells of the osteoblast lineage and consequent RANKL‐induced osteoclastogenesis . Based upon our results a putative mechanism of bone loss in periodontitis is proposed in Figure .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Notch 2 was previously found to play a major role in suppression of osteoblastogenesis and promotion of osteoclastogenesis . This effect was mostly exerted by induction of RANK in cells of the osteoblast lineage and consequent RANKL‐induced osteoclastogenesis . Based upon our results a putative mechanism of bone loss in periodontitis is proposed in Figure .…”
Section: Discussionsupporting
confidence: 65%
“…The bone destruction seen in periodontitis arises as a consequence of an aberrant activation of host immune system and its progression and severity are mainly attributed to complex interactions between bone‐remodeling cells and immunoregulatory mediators . Notch signaling pathway acts as an important regulator of bone‐remodeling processes, both in physiological and pathological conditions, controlling differentiation and functions of the osteoblastic and osteoclastic lineages . This pathway has also a prominent role in the differentiation and function of immunomodulatory cells in innate and adaptive immune response .…”
Section: Discussionmentioning
confidence: 99%
“…Besides its role in muscle physiology (see Section 3.2.2), Notch signaling has also been reported to be involved in skeletal physiology. We and others recently reported that this pathway is mechanosensitive in skeletal precursors [58,114]. Similarly, the Hippo pathway has gained attention as an important pathway in mechanotransduction and skeletal physiology.…”
Section: Principles Of Bone Formation Maintenance and Regenerationmentioning
confidence: 80%
“…Notch activation in committed osteoblasts leads to osteosclerosis by increased immature osteoblasts due to inhibition of terminal differentiation of osteoblast. When Notch signaling is activated in osteocytes, it shows high bone mass due to reducing bone resorption ( Figure 2) [70,[73][74][75][76][77]. Recent studies have shown several interesting mechanistic aspects of Notch function in modulating osteoblast differentiation.…”
Section: Notch Regulation Of Osteoblast Differentiation and Osteocytementioning
confidence: 99%